Is the feminization of labor harmful to agricultural production? The decision-making and production control perspective - Jia-cheng LIU; Zhi-gang XU; Qiu-fen ZHENG; Lillian Hua (Journal of Integrative Agriculture, 2019)
Even today, academics continue to debate the effect of feminization of agricultural labor force on agricultural output. By considering the dimensions of participation in decision-making and production, this study divides the various agricultural production models into three types: (i) the traditional model of decisions made either jointly by men and women or by men alone while both genders participate in production, (ii) complete feminization of agricultural decision-making and the production labor force, and (iii) feminization of the agricultural production labor force only. This study investigates the effects of combining or separating decision-making and production in regard to agricultural development in the context of feminization of the agricultural labor force. Using follow-up data collected from 2004–2008 by the Ministry of Agriculture of China, we built a comprehensive panel data model to test our hypotheses. Our research shows that in comparison to traditional agricultural households and fully feminized agricultural labor forces, partially feminized production resulted in lower grain yield and technological advancement. The feminization of agricultural labor does not necessarily have a negative impact on agricultural output, especially since heavy manual labor is being increasingly replaced by agricultural machinery and outsourcing of tasks. The degree of feminization of the decision-making and production processes should be an important consideration when evaluating the purported negative effects of the feminization of agricultural labor.